Workload efficiency as a new tool to describe external and internal competitive match load of a professional soccer team: A descriptive study on the relationship between pre-game training loads and relative match load - Grünbichler, J.; Federolf, P.; Gatterer, H. (European Journal of Sport Science, 2020)
The current study introduces a new index for external and internal workload, "workload efficiency", and assesses in professional soccer the influence of pre-match training load on match workload efficiency. External and internal workloads were determined for 44 training sessions and 16 competitive matches using a 10-Hz global positioning system (GPS) and a 200-Hz accelerometer/heart rate monitor. Training loads were registered from day five (D-5) to day one (D-1) prior to each competitive match. Workload efficiency was calculated for each match as the ratio between overall external and internal load. A multiple stepwise regression analysis (including z-transformed variables) was used to determine training load variables that predict workload efficiency of the following matches. Training load variables of the previous days explained 26.6% of the variance in workload efficiency during the following matches. Long sprinting distance on D-3 and D-4 and total distance on D-1 positively influenced the players` workload efficiency, whereas long training durations and high training load on D-1 showed adverse effects. The present outcomes suggest that including sprint training (high sprinting distance) four and three days prior to a match, may provide a positive stimulus for the subsequent workload efficiency in matches. The negative impact of long training duration and high training load one day before the game highlights the importance of a diligent planning of the immediate competition preparation phase. This study shows that workload efficiency is a useful metric to assess match performance and that body-worn sensor technology can be useful for tailoring training loads.